Lubricant composition comprising an oxygen-containing polymer

CN123036368APending Publication Date: 2026-11-03DOW GLOBAL TECHNOLOGIES LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480090551.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing lubricants have insufficient fluidity at low temperatures and insufficient viscosity at high temperatures, leading to equipment wear. Furthermore, their performance is unstable at extreme temperatures, making it difficult to meet the high-efficiency operation requirements of air compressors.

Method used

By combining oxygen-containing polymers (such as polyalkylene glycols and polyalkyl methacrylates) with API base oils and nitrogen-containing compound additives, a lubricant composition with high viscosity index, low coefficient of friction and good oxidation stability is formed.

Benefits of technology

It achieves viscosity stability over a wide temperature range, reduces frictional losses, improves the energy efficiency and oxidation stability of the air compressor, and reduces deposit formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention is a lubricant composition comprising at least three components. The first component is a particular oxygen-containing polymer as described herein. The second required component is at least one American Petroleum Institute (API) base oil. The third required component is an additive comprising a nitrogen-containing compound, wherein the nitrogen-containing compound comprises at least one compound selected from the group consisting of an aniline compound (preferably containing a urethane), an amine phosphate compound, and a triazole compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Background technology.

[0002] Air compressors, as a major power source, are widely used in manufacturing and construction industries, and these units are estimated to account for 8% to 10% of industrial power consumption. Air compressor oil is crucial for ensuring the normal operation of air compressors and protecting the system. The main performance requirements for high-quality air compressor oil are appropriate viscosity, good thermal oxidation stability, corrosion resistance, deposit control, and lubrication of moving parts. In rotary screw air compressors (RSACs), the lubricant also acts as a heat transfer fluid to remove the heat generated during compression. Currently, mineral oils and synthetic hydrocarbon oils dominate the air compressor oil market.

[0003] The industry's long-term goal is to develop more energy-efficient lubricants to reduce energy costs and improve the sustainability of air compressors through carbon reduction. Currently, significant innovative efforts are being made in developing lubricants that offer energy efficiency advantages without excessively sacrificing performance.

[0004] One way to improve efficiency is to reduce frictional losses in equipment by developing lubricants that reduce friction between moving parts. This can be achieved, for example, by using friction modifiers and / or selecting base oils with inherently low friction values.

[0005] A second way to improve energy efficiency is simply to reduce the viscosity of the lubricant. Lubricants with lower density, lower drag coefficients, and lower viscosity consume less energy during operation. However, when the viscosity of the lubricant becomes too low, excessive wear can occur on contact surfaces, which can ultimately damage the equipment. The problem of excessive wear can be exacerbated at extreme temperatures, as the oil may not flow fast enough at low temperatures to cover the surface, and may not provide sufficient thickness at high temperatures. Therefore, it is crucial to select a lubricant that ensures optimal viscosity at both low and high temperatures to minimize churning losses.

[0006] Viscosity index (VI) is a measure of how much an oil changes its viscosity with temperature. It is calculated using ASTM D2270 based on the kinematic viscosity at 40°C and 100°C. A higher viscosity index value corresponds to a smaller viscosity change within this temperature range. Lubricants with a high viscosity index are desirable in order to maintain a more consistent viscosity over a wide temperature range.

[0007] Viscosity index improvers are additives that reduce changes in oil viscosity within a certain temperature range. Typical viscosity index improvers include, for example, olefin copolymers (OCP), polyalkyl methacrylate polymers (PAMA), polyalkylene glycols (PAG), and hydrogenated styrene-diene polymers (HSD).

[0008] Other parameters that significantly affect the energy efficiency of air compressor oils include density, heat capacity, and thermal conductivity. Lower density means lower agitation losses. Higher heat capacity (Cp) and thermal conductivity (TC) mean more efficient cooling and lower compressed air temperatures, which translates to less energy consumption at the same discharge pressure. Therefore, lubricants offering low CoF and high VI, Cp, and TC are highly desirable.

[0009] OSPs, partially derived from 1,2-epoxybutane (BO), differ from conventional polyalkylene glycols derived from ethylene oxide (EO) and / or 1,2-epoxypropane (PO) in that they are more compatible with hydrocarbon oils. OSPs are used as co-base oils in hydrocarbons due to their excellent solubility, and they can also be used as friction modifiers (which help improve fuel economy) and deposit control additives (which help extend fluid life).

[0010] US Patent 11,396,638 discloses esterified OSP (E-OSP) and demonstrates that when they are added to hydrocarbon oils, they increase the VI value and further improve frictional properties.

[0011] Antioxidants are commonly found in lubricant formulations. These materials slow down the aging process of lubricants. As lubricants age, they can sometimes form hazardous deposits in equipment. Deposits are common in applications such as air compressor and bus engine oils when hydrocarbon base oils are used as the main component of the formulation.

[0012] The American Petroleum Institute (API) has classified hydrocarbon base oils into Group I, Group II, Group III, and Group IV based on their viscosity index (VI), saturation level, and sulfur level. The following is a description of the composition of Group I through Group V hydrocarbon base oils.

[0013] The American Petroleum Institute classifies these different base petroleum types as follows: Category I, >0.03% by weight of sulfur and / or <90% by volume of saturates, with a viscosity index between 80 and 120; Category II, < 0.03% by weight of sulfur and > A 90% by volume saturated product has a viscosity index between 80 and 120. Class III, < 0.03% by weight of sulfur and > 90% by volume of saturated material, viscosity index >120.

[0014] Category IV, polyalphaolefins.

[0015] Group V, all other base oils, such as polyalkylene glycols, esters, etc.

[0016] The shift towards lower viscosity lubricants is a macro trend in the development of modern automotive lubricants, particularly bus engine oils. Lower viscosity lubricants are known to offer better fuel economy; however, several technical challenges remain. Lower viscosity lubricants are known to typically have a lower viscosity index (VI) value, which is a measure of how the lubricant's viscosity changes with temperature. A lower VI value means that its viscosity decreases more at higher temperatures. A higher viscosity index value is generally preferred, as it allows the lubricant to maintain a small viscosity change as the temperature rises from low to high temperatures, which may occur during equipment operation.

[0017] Recently, a new series of OSPs named UCON have been made commercially available. Unlike conventional PAGs used in lubrication which are derived from ethyleneoxide (EO) and propylene oxide (PO), these OSPs are more compatible with hydrocarbon oils. OSPs are being used as co-base oils in hydrocarbon oils dueto their excellent solubility and they offer excellent functionality and canimprove friction control (which helps fuel economy in automotive lubricants) and control deposit ( Unfortunately, OSPs in the low viscosity range described above typically have low VI values ​​(that is, less than 130) and are therefore less interesting as primary base oils inlubricant formulations.

[0018] A recent publication, WO2019 / 126923, discloses a new class of lubricants that are esterified OSPs (E-OSPs). These materials exhibit significantly higher viscosity indices and lower volatility than their respective parent (i.e., unesterified) OSP base oils. This is especially true at lower viscosity grades, such as those with KV 100 at 4 cSt or even 3 cSt.

[0019] Better additive and base ingredient technologies are needed for lubricant compositions to meet the increasingly stringent requirements of lubricant users. In particular, advanced additive technologies and synthetic base ingredients are needed that offer improved fuel economy, solubility and dispersibility of polar additives or sludge generated during lubricant use, and oxidative stability. Summary of the Invention

[0020] This invention relates to a novel composition that achieves at least some of these objectives. The composition comprises at least three components. The first component is an oxygen-containing polymer, which is one of the following: a) Polyalkylene glycol (PAG) compounds having the following structure: R 1 (C=O) p [O(R 2 O) m (R 3 O) n (C=O) q R 4 ] s Where R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; n and m are each independently zero or a positive integer, where m+n is greater than 30; p and q are each independently 0 or 1; and s is a number ranging from 1 to 4; or b) Polyalkyl methacrylate (PAMA) compounds obtained by polymerizing a mixture of olefinically unsaturated monomers with one or more methacrylates having the following structure: Where R is hydrogen or methyl, R5 is a straight-chain or branched alkyl residue having 1 to 40 carbon atoms, and R6 and R7 are independently hydrogen or groups of the formula -COOR', where R' means hydrogen or alkyl having 1 to 40 carbon atoms; Furthermore, the PAMA has a diameter greater than or equal to 100 mm when measured at 100°C. 2 The kinematic viscosity per s and the flash point at 120°C or higher as determined by ASTM D238.

[0021] The second required component is at least one American Petroleum Institute (API) base oil, selected from the group consisting of: i. Group I base oils, wherein the Group I base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; ii. Group II base oils, wherein the Group II base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iii. Group III base oils, wherein the Group III base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iv. Group IV base oils, wherein the Group IV base oil has a particle size of less than or equal to 8 mm as measured at 100°C. 2 kinematic viscosity per second; v. Group V base oil, which is a polyalkylene glycol (PAG) compound having the following structure: R 1 (C=O) p [O(R2O) f (R 3 O) g (C=O) q R 4 ] s Where: R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; f and g are independently numbers, where f+g is a number ranging from 1 to 25; p and q are numbers ranging from 0 to 1; s is a number ranging from 1 to 4; and The third required component is an additive containing a nitrogen-containing compound, wherein the nitrogen-containing compound comprises at least one compound selected from the group consisting of aniline compounds, phosphate compounds, and triazole compounds.

[0022] The synergistic effect of dithiocarbamates and alkylated diphenylamine (ADPA) in hydrocarbon base oils is known. However, we have found that this combination produces significant deposits in bulk oxidation experiments. We have demonstrated that the addition of oil-soluble polyalkylene glycols to hydrocarbon oils containing specific doses and proportions of dithiocarbamates and diphenylamines results in improved deposit formation and good oxidative stability. This is another aspect of the present invention. Attached Figure Description

[0023] Figure 1 This is a visual representation of the sediment control performance of Comparative Example A (left) and Example 6 (right) after a 25-day oxidation test. Detailed Implementation

[0024] This invention relates to novel lubricant composition raw materials, which have improved fuel economy, solubility and dispersibility in sludge generated during the use of polar additives or lubricating oils, and oxidative stability. The composition comprises at least three components.

[0025] The first component is an oxygen-containing polymer, which is one of the following: a) Polyalkylene glycol (PAG) compounds having the following structure: R 1 (C=O) p [O(R 2 O) m (R 3 O) n (C=O) q R 4 ] s Where R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; n and m are each independently zero or a positive integer, where m+n is greater than 30; p and q are each independently 0 or 1; and s is a number ranging from 1 to 4; or b) A polyalkyl methacrylate (PAMA) compound obtained by polymerizing a mixture of olefinically unsaturated monomers, and one or more methacrylates having the following structure: Where R is hydrogen or methyl, R5 is a straight-chain or branched alkyl residue having 1 to 40 carbon atoms, and R6 and R7 are independently hydrogen or groups of the formula -COOR', where R' means hydrogen or alkyl having 1 to 40 carbon atoms; Furthermore, the PAMA has a diameter greater than or equal to 100 mm when measured at 100°C. 2 The kinematic viscosity per second and the flash point at 120°C or higher, as determined by ASTM D238. Preferably, the PAMA comprises repeating methacrylate units, wherein 0%-80% by weight of the R5 units are C17-C40.

[0026] In some embodiments, the poly(meth)acrylate polymer comprises 1%-30% by weight of R5 units in the C1-C8 range, 50%-95% by weight of R5 units in the C9-C16 range, and 0%-40% by weight of R5 units in the C17-C40 range.

[0027] In some embodiments, the poly(meth)acrylate alkyl polymer comprises at least 40% by weight, preferably 50% by weight, repeating methacrylate units.

[0028] In some embodiments, the polyalkyl methacrylate polymer comprises R5 units having C1-C8, and / or R5 units having C9-C34 methacrylate repeating units, preferably C1-C8 and C9-C24 methacrylate repeating units.

[0029] In some embodiments, the polymethyl methacrylate polymer comprises repeating units derived from dispersant monomers that are olefin unsaturated monomers.

[0030] In some embodiments, the polymethyl methacrylate polymer comprises repeating units derived from styrene, an olefinically unsaturated monomer.

[0031] In some embodiments, the polyalkyl methacrylate polymer comprises repeating units derived from ethoxylated and / or hydroxylated methacrylate monomers.

[0032] In some embodiments, the poly(meth)acrylate polymer has a weight-average molecular weight Mw of 10,000 g / mol to 200,000 g / mol, preferably 20,000 g / mol to 100,000 g / mol.

[0033] In some embodiments, the poly(meth)acrylate polymer has a polydispersity Mw / Mn of 1 to 15, preferably 1.01 to 10, more preferably 1.05 to 5.55.

[0034] In some embodiments, the poly(meth)acrylate polymer compound has a thickness greater than or equal to 100 mm² measured at 100°C. 2 Kinematic viscosity / s, flash point greater than or equal to 120℃, and viscosity index greater than or equal to 120.

[0035] In some embodiments, the poly(meth)acrylate polymer has a permanent shear stability index of less than 30 as defined by ASTM 5621, wherein 10% of the polymer is in a Group II mineral oil; wherein the poly(meth)acrylate polymer has a weight of up to (≤) 30% based on the total weight of the lubricant composition.

[0036] Preferably, the PAG of component a) should have a diameter greater than or equal to 15 mm. 2 / s, more preferably 30mm 2 PAG has a kinematic viscosity of 100 m / s or higher, measured at 100°C. PAG also preferably has a kinematic viscosity of 100 m / s or higher, measured at 40°C. 2 / s, more preferably greater than 150mm 2 / s or even 200mm 2 The kinematic viscosity is 1 / s. For PAG in which the BO:PO weight ratio is 3:1 or less, it is generally preferred that the PAG has a higher kinematic viscosity, for example, a kinematic viscosity greater than or equal to 150 mmHg measured at 40°C. 2 / s, more preferably greater than 200mm 2 / s or even 250mm 2 / s.

[0037] PAGs also preferably have a viscosity index greater than or equal to 130, or even more preferably greater than about 150. For PAGs in which the BO:PO weight ratio is 3:1 or less, it is generally preferred that the PAG has a higher viscosity index, for example greater than 150 or even 200.

[0038] The PAG of component a) is preferably selected such that m and n provide at least 20%, preferably at least 25%, 30%, or even 40% of the target weight ratio of butane oxide to propylene oxide. Generally, when there is less branching (i.e., when s is 2 or even 1), it is preferable to have more BO.

[0039] R 1 and R 4The composition can also be adjusted according to the desired properties of the component. Generally, a larger R group tends to increase viscosity, but it can also have R as hydrogen. In some embodiments, it is preferred that R... 1 and R 4 Each is independently C1 to C4 or C5 to C14.

[0040] In some embodiments, it is preferred that at least one of p and q is equal to 1, because esterification can help increase the viscosity index. In some embodiments, it is preferred that both p and q are equal to 1; however, it is also possible for both p and q to be 0.

[0041] The PAMA used as the first component in the composition of the present invention has a kinematic viscosity greater than or equal to 100 mmHg when measured at 100°C. 2 / s, preferably 150mm 2 / s or even 200mm 2 PAMA also has a flash point of 120°C or higher, preferably 150°C.

[0042] Although component a) or component b) can be used alone, in some embodiments it may be desirable to have both first components a) and b). It is also desirable for the first component to contain more than one substance of component a or component b.

[0043] The second required component is at least one American Petroleum Institute (API) base oil, selected from the group consisting of: i. Group I base oils, wherein the Group I base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; ii. Group II base oils, wherein the Group II base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iii. Group III base oils, wherein the Group III base oil has a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iv. Group IV base oils, wherein the Group IV base oil has a particle size of less than or equal to 8 mm as measured at 100°C. 2 kinematic viscosity per second; v. Group V base oil, which is a polyalkylene glycol (PAG) compound having the following structure: R 1 (C=O) p [O(R2O) f (R3O) g (C=O) q R 4 ]s Where: R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; f and g are independent numbers, where f+g is a number ranging from 1 to 25; p and q are numbers ranging from 0 to 1; s is a number ranging from 1 to 4; Although all base oils can be used in this invention, in some applications, it is preferred that the base oils be selected from ii to v. It is also contemplated that two or more base oils may be used together.

[0044] The third required component is an additive containing a nitrogen-containing compound, wherein the nitrogen-containing compound comprises at least one compound selected from the group consisting of aniline compounds, phosphate compounds, and triazole compounds.

[0045] Preferably, the combined weight of the nitrogen-containing compound is 0.1% to 10% by weight of the total weight of the lubricant composition, more preferably 0.5% to 9% by weight, and even more preferably 1% to 8% by weight.

[0046] In some embodiments, it is preferred that when aniline is selected as the nitrogen-containing compound, a carbamate compound is also added. In this case, the weight ratio of aniline to carbamate is preferably 30:1 to 1:1, and even more preferably 20:1 to 5:1.

[0047] Preferably, the first component (i.e., the oxygen-containing polymer) accounts for 1% to 50% by weight of the total lubricant composition, more preferably 2% to 40% by weight, and even more preferably 3% to 30% by weight. Preferably, the second component (i.e., the base oil) accounts for 40% to 98% by weight of the total lubricant composition, more preferably 50% to 95% by weight, and even more preferably 60% to 90% by weight. Preferably, the third component (i.e., the nitrogen-containing compound) accounts for 0.01% to 10% by weight of the total lubricant composition, more preferably 0.5% to 9% by weight, and even more preferably 1% to 8% by weight.

[0048] The lubricant compositions of the present invention may also contain other additives commonly used in lubrication applications, such as other types of antioxidants, other types of viscosity modifiers (viscosity index improvers), defoamers, demulsifiers, iron-based corrosion inhibitors, brass passivators, pour point depressants, anti-wear additives, extreme pressure (EP) additives, dyes, etc. The total treatment level of all these additives is typically <25%, often <10%, and preferably <5%.

[0049] The total lubricant composition of the present invention is preferably characterized by having a thickness greater than or equal to 10 mm as measured at 40°C. 2 / s, more preferably greater than or equal to 15mm 2 / s or even 20mm 2 The composition preferably has a kinematic viscosity of 130, more preferably 140 or even 150. The composition preferably has a specific heat capacity of 2.05 J / (g∙K), more preferably 2.11 J / (g∙K), or even 2.115 J / (g∙K) at 90°C. The composition preferably has a thermal conductivity of 0.125 W / (m∙K), more preferably 0.128 W / (m∙K), or even 0.130 W / (m∙K) at 90°C. It is also preferred that the total composition has a kinematic viscosity of 1.0 g / cm³ at 25°C. 3 More preferably, less than 0.98 g / cm³ 3 Or even 0.96g / cm 3 The density. It is also preferred that the coefficient of friction of the total composition, as measured by the MTM test, is less than or equal to 0.05, more preferably less than or equal to 0.04, or even 0.03, under conditions of 90°C, 71N load, 10% SRR and a conveying speed of 1000 mm / s.

[0050] Example The following examples can be used to demonstrate the efficacy of the present invention. The following test methods can be used to characterize the present invention: Kinematic viscosity was measured according to ASTM D7042 and D445.

[0051] Viscosity index is measured according to ASTM D2270.

[0052] Pour point is measured according to ASTM D97.

[0053] Table I includes a description of the materials used in these embodiments.

[0054] Table 1. Raw materials used to describe the present invention raw materials The synthesis method of OSP-C is as follows: : Preparation of esterified OSP, or "OSP-C" The esterified OSP sample was synthesized according to the following steps: A solution of UCON OSP-12 (374 g, 1 mol) and n-valeric acid (102 g, 1 mol) in toluene (500 mL) was stirred at room temperature. PTSA (1.90 g, 0.001 mol) was added with stirring, and the mixture was refluxed overnight with Dean-Stark to remove 18.0 mL of water from the system at 135 °C. After the mixture was cooled to room temperature, KOH (1.12 g, 0.002 mol) was added and stirred overnight to neutralize the PTSA. 10 g of magnesium silicate was added and stirred at 60 °C for 3 hours to absorb the salts generated in the system, and then the mixture was filtered through filter paper. After filtration, residual solvent was removed by vacuum distillation to obtain a pale yellow liquid.

[0055] Preparation of Examples Each formulation is prepared by adding the components to the beaker in the following order. Add an oxygen-containing polymer (i.e., OSP, E-OSP, or PAMA). Adding diphenylamine Adding dithiocarbamate Adding any other additives, including additional oxygen-containing polymers. Add a base oil (or, if more than one base oil is available, add multiple oils). The mixture was stirred at 80℃±5℃ for 1 hour until a homogeneous composition was obtained.

[0056] Test methods : The ASTM (American Society for Testing and Materials) test methods are as follows: Kinematic viscosity and density were measured according to ASTM D7042.

[0057] KV40 is the kinematic viscosity at 40°C, measured in cSt.

[0058] KV100 is the kinematic viscosity at 100°C, expressed in cSt.

[0059] Viscosity index is measured according to ASTM D2270.

[0060] Thermal property measurement : Heat capacity (Cp) is measured by DSC (differential scanning calorimetry).

[0061] Thermal conductivity (TC) is measured using a transient hot wire device.

[0062] Friction test method : The frictional force of steel balls rotating on a steel disc was measured using a miniature traction machine (MTM, purchased from PCS Instruments, UK). The steel disc was made of AISI 52100 steel, 45 mm in diameter, with a hardness of 750 HV and Ra < 0.02 μm. The steel balls were made of AISI 52100 steel, 19 mm in diameter, with a hardness of 750 HV and Ra < 0.02 μm. In the standard configuration, the steel balls were loaded onto the surface of the steel disc, and both the balls and the disc were driven independently to control the rolling / slipping ratio. FoC was measured under the following test conditions: Load: 71N Slide / scroll ratio: 10%.

[0063] Carrying speed: 1000mm / s Test temperature: 90℃ The test conditions for the following applications are intended to serve as representative lubrication conditions in compressors.

[0064] Energy efficiency testing methods : Under the same conditions, the energy efficiency of the rotary screw air compressor was tested and compared with the specific power of a comparative example (Comparative Example A). The energy efficiency of Comparative Example D relative to Comparative Example A was measured on a 110 kW RSAC (obtained from United OSD), with a discharge volume of 20 m³ at 8 bar. 3 The energy efficiency of Comparative Examples A to C and Examples 1 to 6 was measured on a 75 kW RSAC (obtained from Atlas Copco), with an exhaust volume of 15 m³ at 7 bar, 8 bar, and 10 bar. 3 The energy efficiency was [value] / min, and the discharge temperature was 85°C. Energy efficiency <0.2% in the test was not considered significant.

[0065] Improved ASTM D2893 test : In the improved test, the test lubricant in a glass tube is heated to 150°C, and air flows through the lubricant at a rate of 30 L / min. The method involves adding a standard iron-copper catalyst coil to the glass container. The total acid number (TAN) is recorded. This test is designed to measure the change in TAN over time (measured in days) compared to a fresh sample. The fluid reaches its "end of service" when the aged sample reaches a value >2.0 mg KOH / g. TAN values ​​are measured after 7, 14, 21, and 25 days. This is a modification of the standard ASTM method.

[0066] Sediment control methods Here, a visual method is used to differentiate sediment control performance. At the end of the test, the fluid is drained from the tube, and the sediment in the glassware is examined and graded. If the inner surface of the glassware shows that more than 50% of the glassware is covered with sediment, it is graded as "heavy sedimentation." If the glassware shows that 20%–50% of the glassware is covered with sediment, it is graded as "moderate sedimentation." If the glassware shows that less than 20% of the glassware is covered with sediment, it is graded as "light sedimentation."

[0067] All embodiments of the present invention contain at least one or more oxygen-containing polymers selected from (PAG) compounds or polyalkyl methacrylate (PAMA) compounds, wherein the weight ratio of butylene oxide to propylene oxide in the (PAG) compound is at least 25%.

[0068] Table 1. Composition of the embodiments of the present invention All comparative examples are commercial formulations characterized by the absence of any oxygen-containing polymers as claimed in claim 1. These materials are believed to contain some diphenylamine but no dithiocarbamates.

[0069] Table 2. Comparison of Embodiments and Comparative Examples of the Invention One way to improve efficiency is to reduce frictional losses between moving parts in the equipment. A second way is to reduce internal friction and agitation losses within the lubricant. A third way is to enable the compressor to operate under optimized conditions (i.e., better heat transfer efficiency, etc.). Therefore, there is a strong need for lubricants with low CoF and low density, as well as high VI, Cp, and TC.

[0070] The viscosity index (VI), coefficient of friction (CoF), specific heat capacity (Cp), and thermal conductivity (TC) of the comparative examples and embodiments of the present invention are compared in Table X. All embodiments of the present invention exhibit significantly better VI, CoF, Cp, and TC compared to comparative example A.

[0071] Comparative Example AD contains base oils of hydrocarbons, synthetic hydrocarbons, and PAG (all without OSP), yet exhibits similar energy efficiency (<0.2%). Comparative Example AD has a VI of 105 to 153, indicating that energy efficiency cannot be achieved simply by controlling the VI.

[0072] Comparative Example A exhibits the lowest density compared to all embodiments of the present invention, indicating that energy efficiency cannot be achieved simply by controlling density.

[0073] Example 1 has a lower viscosity grade compared to Comparative Example A, while Examples 2-5 have a higher viscosity grade compared to Comparative Example A. However, all examples show significant energy efficiency compared to Comparative Example A at 8 bar and 10 bar, indicating that energy efficiency cannot be achieved by simply controlling viscosity.

[0074] Example 1 has a lower viscosity grade than Comparative Example BD, while Examples 2-5 have the same viscosity grade as Comparative Example BD, but all show significant energy efficiency relative to Comparative Example BD.

[0075] Examples 1-5 were based on E-OSP, PAG, and hydrocarbon oil, respectively, but all contained oxygen-containing polymers (OSP, E-OSP, or PAMA). Compared with Comparative Example AD, which was based on hydrocarbon oil, synthetic hydrocarbon base oil, and PAG, they all showed significant energy efficiency.

[0076] All embodiments of the present invention exhibit significant energy efficiency compared to comparative example AD.

[0077] The synergistic effect of dithiocarbamates and alkylated diphenylamine (ADPA) in hydrocarbon base oils has been proposed in the prior art. As shown below, a major drawback was found when using this combination, as it produces a large amount of deposits in bulk oxidation experiments. It has been found that adding oil-soluble polyalkylene glycols to hydrocarbon oils containing a certain dosage and proportion of dithiocarbamates and diphenylamine can improve deposit formation and provide good oxidative stability.

[0078] Table 3. Compositions of the present invention and comparative examples Oxidation lifetime was measured using the modified ASTM D2893 test described in the preceding section. Deposition levels were graded according to the description in the preceding section. Comparative Example E contains an antioxidant combination of diphenylamine and dithiocarbamate. Despite its excellent oxidation lifetime of more than 25 days, it exhibited heavy deposition.

[0079] Comparative Example F shows a hydrocarbon oil containing OSP and various antioxidant packages; and a hydrocarbon oil without carbamates. This package is a known combination of antioxidants (phenylnaphthylamine and diphenylamine) commonly used in the lubricant industry. Its oxidation life is significantly shorter than that of Comparative Example E.

[0080] Comparative Example G shows the same formulation as Comparative Example E, but replaces 18.0% of the hydrocarbon oil with OSP-A. Although not within the scope of this invention because the oxygen-containing polymer in this particular example does not meet the requirement of m+n>30, this example is included to demonstrate the synergistic effect of urethane and diphenylamine. This effect is expected to continue in the embodiments of this invention. As shown in Table 3, Comparative Example G exhibits excellent oxidation lifetime greater than 25 days and demonstrates excellent deposit control (mild deposition). Figure 1 This is a visual representation of the results, with Comparative Example E on the left and Example 6 on the right.

Claims

1. A lubricant composition comprising: a. At least one oxygen-containing polymer selected from the group consisting of: i. Polyalkylene glycol (PAG) compounds having the following structure: R 1 (C=O) p [O(R 2 O) m (R 3 O) n (C=O) q R 4 ] s Where R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; n and m are each independently zero or a positive integer, where m+n is greater than 30 and less than 500; p and q are each independently 0 or 1; and s is a number ranging from 1 to 4; and ii. A polyalkyl methacrylate (PAMA) compound obtained by polymerizing a mixture of olefinically unsaturated monomers, and one or more methacrylates having the following structure: Where R is hydrogen or methyl, R5 is a straight-chain or branched alkyl residue having 1 to 40 carbon atoms, and R6 and R7 are independently hydrogen or groups of the formula -COOR', where R' means hydrogen or alkyl having 1 to 40 carbon atoms; And the PAMA described therein has a diameter greater than or equal to 100 mm as measured at 100°C. 2 The kinematic viscosity per second (k / s) and the flash point at 120°C or higher as determined by ASTM D238. And the PAMA described therein has a diameter greater than or equal to 100 mm as measured at 100°C. 2 The kinematic viscosity per second and the flash point at or above 120°C; b. At least one American Petroleum Institute (API) base oil, selected from the group consisting of: i. Group I base oils, wherein the Group I base oils have a thickness of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; ii. Group II base oils, wherein the Group II base oils have a particle size of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iii. Group III base oils, wherein the Group III base oils have a particle size of less than or equal to 46 mm as measured at 40°C. 2 kinematic viscosity per second; iv. Group IV base oils, wherein the Group IV base oils have a particle size of less than or equal to 8 mm as measured at 100°C. 2 kinematic viscosity per second; v. Group V base oils, which are selected from the group consisting of:

1. A polyalkylene glycol (PAG) compound having a weight ratio of butylene oxide to propylene oxide of at least 25% (BO:PO≥) and having a thickness of 2 mm as measured at 100°C. 2 / s-20mm 2 kinematic viscosity per s, measured at 40°C in 8 mm² 2 / s-100mm 2 The PAG has a kinematic viscosity of / s and a viscosity index greater than or equal to 120, wherein the PAG has the following structure: R 1 (C=O) p [O(R2O) f (R 3 O) g (C=O) q R 4 ] s Where: R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; f and g are independently numbers, where f+g is a number ranging from 1 to 25, and f and g are selected to provide a target weight ratio of at least 25% butylene oxide to propylene oxide; p and q are numbers ranging from 0 to 1; s is a number ranging from 1 to 4; and 2. A polyalkylene glycol (PAG) compound having a butane oxide to propylene oxide weight ratio of less than 25%, and having a kinematic viscosity of 2 mm² / s to 20 mm² / s measured at 100°C, a kinematic viscosity of 8 mm² / s to 100 mm² / s measured at 40°C, and a viscosity index greater than or equal to 120, wherein the PAG has the following structure: R 1 (C=O) p [O(R2O) f (R 3 O) g (C=O) q R 4 ] s Where: R 1 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or is hydrogen; R 2 O and R 3 O refers to a monomer selected from 1,2-epoxypropane and 1,2-epoxybutane, and can be in block or random form; R 4 It is a straight-chain or branched alkyl or aryl group having 1 to 18 carbon atoms, or hydrogen; f and g are independent numbers, where f+g is a number ranging from 1 to 25, and f and g are selected to provide a target weight ratio of less than 25% of butylene oxide to propylene oxide; p and q are numbers ranging from 0 to 1; s is a number ranging from 1 to 4; as well as c. An additive package containing a nitrogen-containing compound, wherein the nitrogen-containing compound comprises at least one compound selected from the group consisting of: i. Aniline compounds ii. Ammonium phosphate compounds, and iii. Triazole compounds The combined weight of the nitrogen-containing compounds is 0.50% to 9.5% by weight of the total weight of the lubricant composition.

2. The lubricant composition of claim 1, wherein the nitrogen-containing compound comprises an aniline compound, and the aniline compound is added as a mixture with one or more urethane compounds, and wherein the mixture has a weight ratio of aniline to urethane in the range of 30:1 to 1:

1.

3. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a.i), and the compound has a thickness greater than or equal to 30 mm as measured at 100°C. 2 Kinematic viscosity per s, measured at 40°C and greater than or equal to 200 mm³ / s 2 Kinematic viscosity per s and viscosity index greater than or equal to 150.

4. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises a. i) a compound, and wherein m+n is less than or equal to 500.

5. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises a. i) a compound, and wherein neither m nor n is zero.

6. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises a. ii) a compound having a particle size greater than or equal to 200 mm at 100°C. 2 kinematic viscosity / s.

7. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises the compound of a. i), and m and n are selected to provide a target weight ratio of at least 25% butylene oxide to propylene oxide.

8. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA comprises a repeating methacrylate unit, wherein 0%-80% by weight of the R5 unit is C17-C40.

9. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA comprises 1%-30% by weight of R5 units in the C1-C8 range, 50%-95% by weight of R5 units in the C9-C16 range, and 0%-40% by weight of R5 units in the C17-C40 range.

10. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA comprises at least 50% by weight of repeating methacrylate units.

11. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises a. ii) of the compound, and the PAMA comprises both R5 units having C1-C8 and R5 units having C9-C34.

12. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises a. ii) of the compound, and the PAMA comprises a repeating unit derived from a dispersant monomer that is the olefin unsaturated monomer of the claim 1.

13. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises a. ii) of the compound, and the PAMA comprises a repeating unit derived from styrene as the olefinic unsaturated monomer.

14. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the polyalkyl methacrylate polymer comprises repeating units derived from ethoxylated and / or hydroxylated methacrylate monomers.

15. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA has a weight-average molecular weight Mw in the range of 20,000 g / mol to 100,000 g / mol.

16. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA is characterized by having a polydispersity Mw / Mn in the range of 1.05 to 5.

55.

17. The lubricant composition according to claim 1, wherein the oxygen-containing polymer comprises the compound of a. ii), and the PAMA is characterized by having a diameter greater than or equal to 100 mm as measured at 100°C. 2 Kinematic viscosity / s, flash point greater than or equal to 120℃, and viscosity index greater than or equal to 120.

18. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises the compound of (a. ii), and the PAMA is characterized by having a permanent shear stability index of less than 30 as defined by ASTM 5621, wherein 10% of the polymer is in a Group II mineral oil.

19. The lubricant composition of claim 1, wherein the oxygen-containing polymer comprises a. ii) of the compound, and the PAMA accounts for no more than 30% by weight of the total weight of the lubricant composition.

Citation Information

Patent Citations

  • Modified oil soluble polyalkylene glycols

    US11396638B2

  • Modified oil soluble polyalkylene glycols

    WO2019126923A1